The Fall of Wage Flexibility : Labor Markets and Business Cycles in Latin America and the Caribbean since the 1990s - Lederman, D. (World Bank, Washington, DC, 2016)
This study explores how labor markets have adjusted to temporary business cycle fluctuations since (at least) the 1990s. It focuses on how changes in macroeconomic conditions affect the evolving nature of labor-market adjustments on the other hand. The study pays particular attention to the role of low inflation and international trade in shaping labor-market adjustment. The main focus of the report is on employment, wages and informality. The report analyzes how they are affected by business cycles, and on how low inflation and the nature of external shocks affects labor market dynamics. It is organized as follows. Chapter 1 provides an overview of the cyclical macroeconomic behavior of wages in four LAC countries. Importantly, rather than examining the average cyclical pattern of wages, it focuses on the time varying patterns in the relationship between wages, employment and output. The second part of Chapter 2 studies downward wage rigidities with sectoral data. Chapter 3 moves from wages to quantitative labor-market adjustments and attempts to the answer what limits the expansion of formal employment in LAC? The chapter studies differences, similarities and linkages between formal and informal employment over the business cycle to understand the frustrating persistence of informal employment in the region. Chapter 4 takes a close look at the adjustment of formal labor markets in Northern Mexico during the United States recession of 2008-09. Chapter 5 turns our attention to the distributional costs of recessions by examining how returns to schooling fluctuate with the business cycle, and how they respond to different types of economic shocks. Chapter 6 concludes with a brief summary of the findings and some thoughts about policy implications.